ELF Pedagogy in Spain and the UK - Pineda-Hernández, Inmaculada Concepción (My University, 2018)
Our research project shows that exposing ELT practitioners to language change and to reflective attitudes towards language and towards new developments in ELT methodology can in return help them envisage an ELF aware pedagogical approach. Our research project has three phases: a) understanding pre-service ELT practitioners’ attitudes towards ELF and ELF Pedagogy; b) analyzing in-service ELT practitioners’ attitudes towards ELF and ELF Pedagogy; c) Observing and assessing classroom implementations of ELF-aware strategies. We are currently conducting the second stage. Educational context, teachers’ experience, and field of expertise affect the level of understanding and commitment to ELF Pedagogy. A comparison between both institutions will be presented together with data addressing the differences between the first and the second stages of the project.
Keywords: Inglés - Estudio y enseñanza - Congresos; Inglés como lingua franca; Pedagogía del Inglés como Lingua Franca